Neuroscientific Insights into Islamic Early Childhood Education Management: Enhancing Reasoning Development - Kabul Suprayitno; Sanjaka Yekti; Ahmadi Ahmadi; Abdunrorma Samaalee (Bidayatuna Jurnal Pendidikan Guru Mandrasah Ibtidaiyah, 2025)
This study aims to explore how management practices in Islamic Early Childhood Education (ECE) can enhance reasoning development among children through a neuroscience-informed approach. The research integrates the neuroscience of reasoning, Islamic pedagogical principles, and educational management theory to analyze how structured, faith-based environments influence cognitive and moral growth. Previous studies have emphasized curriculum design and teacher professionalism in Islamic ECE; however, few have examined the managerial dimensions that align pedagogical planning with brain-based learning. This study bridges that gap. This qualitative field research was conducted at BA ‘Aisyiyah Pacitan, employing observation, documentation, and semi-structured interviews with teachers, parents, and administrators. Data were analyzed using Miles and Huberman’s interactive model data reduction, display, and conclusion drawing. The findings illuminate how effective management rooted in Islamic ethics and informed by neuroscience supports the optimal development of reasoning abilities in young children. This study proposes a new model of Neuro-Islamic Education Management that harmonizes brain-based strategies with Islamic moral pedagogy in early childhood education.